Systematic Literature Review of Climate Change Governance Activities of Environmental Nongovernmental Organizations in Southeast Asia. - Haris, Siti Melinda; Mustafa, Firuza Begham; Raja Ariffin, Raja Noriza (Environmental Management, 2020)
Environmental nongovernmental organizations (ENGOs) are considered key players for engendering good climate change governance to address both climate change and sustainable development. The participation of ENGOs in climate change governance occurs in a four-phase policy cycle. They include (1) identification of policy options, (2) policy formulation, (3) policy implementation, and (4) policy monitoring and evaluation. The ENGOs, however, have been criticized for their lack of effectiveness, and their roles in tackling climate change remain unclear. To date, the study on the roles and activities of Southeast Asian ENGOs in climate change governance has been under-researched. This study, therefore, applies a systematic literature review of 19 published articles from Scopus and Web of Science-indexed journal to understand the current state of the Southeast Asian ENGOs participation in climate change governance based on the four-phase policy cycle. The findings show that the ENGOs in Southeast Asia are involved directly and indirectly in climate change governance. They are significant actors in the implementation of the climate change policy, but they play a minimal role in the formulation of said policy. It implies that they could also be a vital partner to the government in the climate change governance process as they can bring effective policy improvements. Lastly, this review will recommend future avenues of research for scholars.